2021
DOI: 10.1177/03611981211014888
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Relationship between Fatigue and Unsafe Behavior of Urban Rail Transit Drivers

Abstract: In recent years there has been rapid development of urban rail transit in China. The train driver, as the direct controller of the train, plays an important role in subway operation, and their driving performance directly determines whether the train is safe or not. To explore the relationship between fatigue and unsafe behavior, a simulated driving experiment was designed to record the train driver’s behavior under fatigue and normal state. The changes of operation accuracy and timeliness are used in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…You et al used an analog driving experiment to explore the relationship between driver's fatigue and behaviour. The results indicated that when the train driver is in the fatigue state, the operation accuracy was 126% lower than the normal state, and in the operation timeliness index, the time required for train drivers to respond and complete actions increased by 28.13% and 17.7%, respectively, compared with the normal state [ 47 ]. Other studies research train driver behaviour at different fatigue levels.…”
Section: Consequences Of Train Driver Fatigue and Distractionmentioning
confidence: 99%
“…You et al used an analog driving experiment to explore the relationship between driver's fatigue and behaviour. The results indicated that when the train driver is in the fatigue state, the operation accuracy was 126% lower than the normal state, and in the operation timeliness index, the time required for train drivers to respond and complete actions increased by 28.13% and 17.7%, respectively, compared with the normal state [ 47 ]. Other studies research train driver behaviour at different fatigue levels.…”
Section: Consequences Of Train Driver Fatigue and Distractionmentioning
confidence: 99%